2006
DOI: 10.1091/mbc.e06-03-0245
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tubulin Is Required for Proper Recruitment and Assembly of Kar9–Bim1 Complexes in Budding Yeast

Abstract: Microtubule plus-end-interacting proteins (؉TIPs) promote the dynamic interactions between the plus ends (؉ends) of astral microtubules and cortical actin that are required for preanaphase spindle positioning. Paradoxically, ؉TIPs such as the EB1 orthologue Bim1 and Kar9 also associate with spindle pole bodies (SPBs), the centrosome equivalent in budding yeast. Here, we show that deletion of four C-terminal residues of the budding yeast ␥-tubulin Tub4 (tub4-⌬dsyl) perturbs Bim1 and Kar9 localization to SPBs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 39 publications
6
45
0
Order By: Relevance
“…Leisner et al (18) showed that sumoylation occurs during metaphase and that Kar9p(4R) fails to localize to only one of the spindle pole bodies. It was further shown that the Bim1p-Kar9p complex assembles before loading onto the microtubules via the spindle pole bodies (37). Here, we have demonstrated that Kar9p sumoylation is important for complex formation with Bim1p.…”
Section: Aurora B-dependent Phosphorylation Of Bim1p Impairsmentioning
confidence: 51%
“…Leisner et al (18) showed that sumoylation occurs during metaphase and that Kar9p(4R) fails to localize to only one of the spindle pole bodies. It was further shown that the Bim1p-Kar9p complex assembles before loading onto the microtubules via the spindle pole bodies (37). Here, we have demonstrated that Kar9p sumoylation is important for complex formation with Bim1p.…”
Section: Aurora B-dependent Phosphorylation Of Bim1p Impairsmentioning
confidence: 51%
“…Significance and P-values were derived using Student's t-test. For high-intensity fluorescent images involving densely packed tissue, the Volocity software uses voxel intensity measurements to quantify cell number (Cuschieri et al 2006). For larval brains stained with anti-Dachshund antibodies, confocal image stacks were acquired using the same settings for all samples, with a gain of 815.…”
Section: Fly Stocks and Genetic Experimentsmentioning
confidence: 99%
“…After 30 min., samples were taken every 15 min and fixed in 70% ethanol. Stu2-VFP in fixed cells (Figure 7) was imaged with a WaveFX spinning disk confocal microscope (Quorum Technologies, Guelph, Ontario, Canada) as described previously (Cuschieri et al, 2006) without agar pads. Optical sections (0.5 m) were acquired through a Ϯ2.5-m z-plane (total of 5.0-m stack) by using Volocity 3DM acquisition software (Improvision, Conventry, United Kingdom).…”
Section: Microscopic Analysesmentioning
confidence: 99%
“…Cells were mounted on a prewarmed 30°C heated stage and allowed to equilibrate for 15 min before imaging. Multichannel four-dimensional imaging of Spc29-CFP and Stu2-VFP fluorescent fusion proteins was performed using a WaveFX spinning disk confocal system (Quorum Technologies) as described previously (Cuschieri et al, 2006). A Tokai Hit stage warmer was used to shift cells from 25 to 30°C, image acquisition commenced 15 min after the stage reached 30°C.…”
mentioning
confidence: 99%